How professional services firms dodged disruption - Birkinshaw, Julian M.; Lancefield, David (MIT Sloan Management Review, 2023)
Big professional services firms appeared to be in the crosshairs of new, technology-fueled competitors a decade ago - but many have maintained or even bolstered their positions. How they did so holds lessons for other incumbents aiming to counter threats that are disruptive to their businesses.
"Summer 2023 issue, vol. 64, no. 4. Reprint #64405.". - Includes bibliographical references
Keywords: Risk management; Professional corporations -- Risk management; Gestion du risque; Sociétés civiles professionnelles; Gestion du risque; risk management